2013
DOI: 10.4103/0019-5049.115616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of low dose intravenous dexmedetomidine on characteristics of spinal anaesthesia with hyperbaric bupivacaine

Abstract: Aims:Intravenous (IV) dexmedetomidine with excellent sedative properties has been shown to reduce analgesic requirements during general anaesthesia. A study was conducted to assess the effects of IV dexmedetomidine on sensory, motor, haemodynamic parameters and sedation during subarachnoid block (SAB).Methods:A total of 50 patients undergoing infraumbilical and lower limb surgeries under SAB were selected. Group D received IV dexmedetomidine 0.5 mcg/kg bolus over 10 min prior to SAB, followed by an infusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 15 publications
15
52
1
Order By: Relevance
“…Dexmedetomidine is increasingly used as an adjunct to various regional techniques [3][4][5][6][7][8]. There are studies on its successful use to facilitate laryngoscopic endotracheal intubation without using muscle relaxant [9,10], and fiber optic guided intubation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine is increasingly used as an adjunct to various regional techniques [3][4][5][6][7][8]. There are studies on its successful use to facilitate laryngoscopic endotracheal intubation without using muscle relaxant [9,10], and fiber optic guided intubation [11].…”
Section: Introductionmentioning
confidence: 99%
“…7,9,15 Our observation of easy reversibility is supported by these workers. Harsoor et al 4 observed that hypotension did not warrant stoppage of infusion of Dex. The incidence of bradycardia was higher in group I (20%) than in group II (11.4%), but statistically it was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…A ceiling effect for analgesia is reported at 0.5 µg/kg/hr of Dex. 4 Ok et al 13 have reported prolongation of sedation (Bispectral Index score 60-80) time with increasing maintenance doses (90 min for 0.2 and 120 min for 0.4 µg/kg/hr) following a bolus dose of Dex of 1 µg/ kg even for patients who receive final anesthesia with 13 mg bupivacaine. Duration of block and rescue analgesia was not studied in their report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dexmedetomidine, a highly specific centrally acting alfa-2 agonist, was used in our study for sedation, improving patient satisfaction and analgesia without causing respiratory depression. [18][19][20] In parasacral approach to sciatic nerve block, pudendal nerve would be blocked and there is a possibility of urinary retention. The incidence of urinary retention is <5% 6 in the literature.…”
Section: Type Of Proceduresmentioning
confidence: 99%